Discovery of new indolosesquiterpenoids bearing a N-O linkage by overexpression of LuxR regulator in a marine bacterium Streptomyces sp. - Park, Jiyoon; Cho, Hang Su; Moon, Dong Hyun; Lee, Donghoon; Kal, Youngjoo; Cha, Sangwon; Lee, Sang Kook; Yoon, Yeo Joon; Oh, Dong-Chan (Frontiers in Marine Science, 2023)
The xiamycins are bioactive indolosesquiterpenoids that have been isolated from actinobacterial strains belonging to the Streptomyces genus. The overexpression of orf2011, which encodes the LuxR family regulator in a marine Streptomyces strain (HK18) isolated from a hypersaline saltern, significantly increased the production of xiamycin dimers, namely the previously reported dixiamycins A and C (3 and 4), compared to the wild-type strain. In addition, the engineered strain produced new members of the xiamycin family (lipoxiamycins A and B), which possessed a lipophilic chain linked to the indolosesquiterpenoid core structure by a N–O bond. The transcription analysis of the N-hydroxylase-encoding xiaH by semiquantitative reverse transcription polymerase chain reaction (RT-PCR) revealed that the transcription level of xiaH responsible for the formation of a nitroxyl radical was increased by the overexpression of orf2011, which is located outside the xiamycin biosynthetic gene cluster. The structures of these compounds were determined by full spectroscopic analysis, and the connectivity between the lipophilic chain and the indolosesquiterpenoid moiety was confirmed in both lipoxiamycins A and B (1 and 2) by MS/MS analysis. Moreover, the absolute configurations of these compounds were established using quantum mechanics-based electronic circular dichroism and DP4 calculations. Finally, it was demonstrated that lipoxiamycin A (1) displayed inhibitory activity against lipopolysaccharide-induced NO production at an IC50 of 9.89 ± 0.92 µM in RAW 264.7 cells.